Analysis of the Training Needs Identification of the Beneficiary Group (KPP) of the PNPM Pisew Program in Bengkulu Province - Indra Utama (Journal of Indonesian Management, 2021)
The objective of this research is to Acquire Preview Performance Recovery Group and maintainer, Knowing gaps/ inadequacies Recovery Working Group and maintainer, Identify training needed by administrators and custodians Recovery Group. This research is a descriptive study with a qualitative approach. Data were collected through questionnaire to 30 respondents and conducted interviews to 4 people and 4 Sub Working Group Facilitator District. Based on the results of the study found that the respondents (administrators group users and custodians) gives value - average overall element to the performance of groups of users and custodians are 2, 36 which means Not Good. Of the five elements / variables under study is related to availability of performance planning and budgeting infrastructure maintenance activities, the controlled utilization and maintenance of infrastructure, contributions of users as well as from the others is manageable, the availability of physical progress reports on a regular basis, the availability of technical skills of construction. For elements - elements that need to be improved, then the required training in order to cover a gap between the ideal performance/ standards organization with actual performance.